2016
DOI: 10.1186/s13104-016-2141-0
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in pregnant women facing prenatal screening may explain their intention to use a patient decision aid: a short report

Abstract: BackgroundIt has been suggested that health literacy may impact the use of decision aids (DAs) among patients facing difficult decisions. Embedded in the pilot test of a questionnaire, this study aimed to measure the association between health literacy and pregnant women’s intention to use a DA to decide about prenatal screening. We recruited a convenience sample of 45 pregnant women in three clinical sites (family practice teaching unit, birthing center and obstetrical ambulatory care clinic). We asked partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
(34 reference statements)
3
33
0
Order By: Relevance
“…Fourth, health literacy was not a factor that influenced women’s intention in our study, although many studies have shown associations between health literacy and related notions, such as patient involvement in decision making [27,38,40-43,47,68]. Hence, a single population based DA implementation program would benefit any pregnant women in the province of Quebec to help them make informed values-congruent decision about prenatal screening for Down syndrome.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Fourth, health literacy was not a factor that influenced women’s intention in our study, although many studies have shown associations between health literacy and related notions, such as patient involvement in decision making [27,38,40-43,47,68]. Hence, a single population based DA implementation program would benefit any pregnant women in the province of Quebec to help them make informed values-congruent decision about prenatal screening for Down syndrome.…”
Section: Discussionmentioning
confidence: 73%
“…After watching the whole video, eligible women answered the Web-based questionnaire based on the TPB but which included additional psychosocial factors known to influence the uptake of a new behavior [57,60-63]. In a previous step of the project, we had conducted a pilot study to validate this questionnaire [68]. We also measured underlying salient beliefs related to the direct constructs as elicited in a previous qualitative study (Leiva Portocarrero, M.…”
Section: Methodsmentioning
confidence: 99%
“… 23 It has high sensitivity, but it can misclassify people with adequate HL. 29 SILS: it asks patients how often they need help when reading health instructions. The response is recorded on a 5-point Likert-type scale (1-never, 2-rarely, 3-sometimes, 4-often and 5-always) and categorised as adequate or inadequate.…”
Section: Methodsmentioning
confidence: 99%
“…This tool has been validated for the Hispanic population residing in the United States. It has high sensitivity, but it may misclassify people with adequate literacy [35]. This tool has also been validated for the Spanish speaking population, with moderate reliability (Cronbach α = 0.69) [22].…”
Section: Data Collectionmentioning
confidence: 99%